Recontextualising Cellular Respiration in Upper Secondary Biology Education. Characteristics and Practicability of a Learning and Teaching Strategy. Issue 3 (2nd July 2016) - Wierdsma, Menno; Knippels, Marie-Christine; van Oers, Bert; Boersma, Kerst
Abstract : Since concepts may have different meanings in different contexts, students have to learn to recontextualise them, i.e. to adapt their meanings to a new context. It is unclear, however, what characteristics a learning and teaching strategy for recontextualising should have. The study aims to develop such a learning and teaching strategy for cellular respiration. The strategy consists of a storyline, consisting of three contexts, with embedded cognitive elements and some episodes focussed on recontextualising cellular respiration. Testing the strategy in two classes in upper secondary biology education showed that the strategy was largely practicable.